Integrating project-based blended learning and design thinking to enhance creativity and openness to experience - Wang, Xiaoqing; Ratanaolarn, Thanin; Sitthiworachart, Jirarat (My University, 2025)
Entrepreneurship education fosters economic growth and career development, yet innovative learning methods and research on openness to experience and creativity remain underexplored in higher vocational education. This study proposes the PjBBL-DT learning model and evaluates its impact on openness to experience and creativity through a 15-week 3-phase quasi-experiment with 61 first-year Chinese vocational students, using PjBBL model in Phase I and PjBBL-DT model in Phases II-III. Five experts evaluated the model, with mean and standard deviation scores indicating high quality. Repeated measures MANOVA revealed a significant improvement in creativity in Phase II, with no significant difference between Phases II and III, suggesting both immediate effects and retention. Openness to experience increased progressively across phases, demonstrating significant improvement but limited retention effect. The findings confirm the model's effectiveness in entrepreneurship education for higher vocational colleges.
Keywords: creativity; Curriculum Studies; design thinking; Higher Education; openness to experience; PjBBL-DT model; Project-based blended learning; Teaching and Learning